Características agronômicas e tecnológicas do sorgo sacarino em diferentes densidades de plantas e espaçamentos entre linhas - Borsoi, Augustinho (2015)
Plants spaced by an equal distance compete minimally for nutrients, light and other factors, thus, proper spatial distribution of the plants is essential to maximize the performance of the crop. In this sense, the aim of this study was to evaluate the agronomic and technological performance of sweet sorghum at different row spacings and plant densities. The experiment was conducted in the experimental area of the State University of West Paraná (UNIOESTE) in Marechal Candido Rondon-PR, in the summer crop of 2013/2014 and second crop of 2014/2015. The experimental design consisted of randomized blocks in a 4x4 factorial scheme, with four spacings (0.25, 0.5, 0.8 and 1.0 m between rows) and four plant densities (50, 75, 100 and 125 thousand plants ha-1). We evaluated the following parameters: plant height, stem diameter, number of tillers, number and length of internodes, total dry mass, productivity and Brix content. In the second crop we also assessed the percentage of saccharose and the total sugar recoverable. The results showed the influence of row spacing on the production of stems and plant dry mass. Smaller spacings provided better results in both seasons (2013/14 and 2014/15). In the second crop, the production of stems ranged from 12.2 to 50.8 t ha-1 in 2013 and from 9 to 51 t ha-1 in 2014. As for the normal growing season 2013/14, the average production of stems was 92.67 t ha-1, whereas in the season 2014/15 production was 83.32 t ha-1. There was no significant difference (p ≤ 0.05) in what concerns to Brix in the summer crops (average 20.5 °Bx) and in the second crop the average Brix content was 12.2 °Bx. Smaller spacings resulted in better agronomic characteristics and technological